2004
DOI: 10.1364/ol.29.000872
|View full text |Cite
|
Sign up to set email alerts
|

Goos–Hänchen shifts at the interfaces between left- and right-handed media

Abstract: The Goos-Hänchen shift caused by total internal reflection at the interface between two media is analyzed. For two media of the same handedness the Goos-Hänchen phase shift opposes the phase variation associated with propagation through the incident medium. The Goos-Hänchen lateral shift is in the same direction as the horizontal component of the incident energy flux. Conversely, for two media of opposite handedness the Goos-Hänchen phase shift reinforces the phase variation associated with propagation through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 11 publications
0
54
0
Order By: Relevance
“…The GH shift is usually proportional to the penetration depth at the order of a wavelength. Many attempts have been made to achieve large lateral shifts (positive or negative) under different circumstances, such as absorbing media [4,9], atomic resonant absorptive vapors [12,16], resonant artificial structures [7,[17][18], negative-permittivity media [19][20], negatively refractive media [21][22][23][24][25][26][27][28], dielectric slabs [8,[29][30], multi-layered structures [6,[31][32]. Recently Li [8] found that the lateral shift of a light beam passing through a lossless transmitting slab could be negative due to the interference between the reflected waves from the slab's two interfaces.…”
mentioning
confidence: 99%
“…The GH shift is usually proportional to the penetration depth at the order of a wavelength. Many attempts have been made to achieve large lateral shifts (positive or negative) under different circumstances, such as absorbing media [4,9], atomic resonant absorptive vapors [12,16], resonant artificial structures [7,[17][18], negative-permittivity media [19][20], negatively refractive media [21][22][23][24][25][26][27][28], dielectric slabs [8,[29][30], multi-layered structures [6,[31][32]. Recently Li [8] found that the lateral shift of a light beam passing through a lossless transmitting slab could be negative due to the interference between the reflected waves from the slab's two interfaces.…”
mentioning
confidence: 99%
“…If the wave is incident into a lefthanded medium and then reflected, the lateral displacement, which is opposite to that in the ordinary Goos-Hänchen effect, will result from the negativity in the refractive index. Then one can demonstrate the atomic-vapor negative refraction by taking advantage of such a negative Goos-Hänchen shift effect [10,[51][52][53].…”
Section: Some Problems In Experimental Verification Of Double-negativmentioning
confidence: 99%
“…When electromagnetic waves propagates in such medium, its electric, magnetic and wave vector will form the three left-handed helical relationship, so Veselago named such medium as left-handed media. In recent years, with the negative refractive index materials of microwave synthetic has become the truth [2], the study of negative refractive index materials has become the focus in international academic physics and electromagnetism [3][4][5][6][7].In 2002, G.V.Eleftheriades in University of Toronto with his team used transmission line theory proved that in two-dimensional transmission line network load shunt inductor L and capacitor C in series consisting of a high -pass LC transmission line network under certain conditions have a negative [8][9] permittivity and negative permeability by such network elements constitute a twodimensional left-handed dielectric waveguide This paper mainly studies the propagation characteristics in planar waveguide with left-hand materials in the case of electromagnetic waves in two-dimensional, the mode of transmission with left-hand materials is analyzed theoretically, Simulation analysis has also been made on the propagation characteristics in planar waveguide with left-hand materials. Compared to traditional media planar dielectric waveguide, the planar waveguide with left-hand materials has better propagation properties.…”
Section: Introductionmentioning
confidence: 99%